PENGARUH UMUR BIBIT DAN UMUR PANEN TERHADAP PERTUMBUHAN DAN PRODUKSI HIDROPONIK NFT TANAMAN SELADA (Lactuca sativa L.) VARIETAS GRAND RAPIDS - Titik Irawati; Slamet Widodo (Jurnal Ilmiah Hijau Cendekia, 2017)
The crowded of agricultural land becomes one of the reasons hydroponic cultivation is considered possible to make use of the best available land. The important thing in hydroponic cultivation is efficiency using nutrients, using modules, and maximum results. The study was conducted in a green house located in DusunSumberKepuhDesaButuhKras District Kediri in January to March 2017. The goal of this research is to determine effect age of seed and age of harvest on growth and production hydroponic Lettuce Green (Lactuca sativa L) varieties Grand rapied. This research use Completely Randomized Design (RAL) with 2 factors. Factor one is the age of seeds consists of 3 levels and factor two is the harvest age consisting of 3 levels. The results of this study were: 1) seedlings treatment take effect significantly to height plants aged 11, 18, and 25 days after plan, number of leaves aged 11, 18, and 25 days after plan, fresh weight every plant, and fresh weight every plot; 2) age of harvest treatment had a very significant effect on fresh weight every plant and fresh weight every plot.